2019
DOI: 10.20945/2359-3997000000160
|View full text |Cite
|
Sign up to set email alerts
|

Pegvisomant in acromegaly: a multicenter real-life study in Argentina

Abstract: Objective: To describe the long term safety and efficacy of pegvisomant (PEGV), and the predictors of treatment response in patients with acromegaly in the real life setting. Subjects and methods: We retrospectively reviewed the clinical, hormonal and radiological data of acromegalic patients treated with PEGV in 17 Argentine centers. Results: Seventy-five patients (age range 22-77, 51 females) with acromegaly have been treated with PEGV for up to 118 months (median 27 months). Before PEGV, 97.3% of patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
4
9
0
5
Order By: Relevance
“…Overall, IGF-I control was observed in 71.7% of patients on pegvisomant monotherapy, with tumor growth noted in 7.3% and transaminase elevation in 3.0%. Real-word experiences independent of ACROSTUDY also mirrored these results, despite some country-specific differences in how pegvisomant is used in monotherapy vs combination therapy regimens [78][79][80]°I n 1,762 patients in ACROSTUDY, 29% of whom had DM at baseline (HbA1c ≥ 6.5%, FBG > 200 g/dL, or use of antidiabetic medication) [81], cross-sectional analysis at 4 years of follow-up showed that FBG and HbA1c remained stable in patients without DM, but prevalence of impaired glucose tolerance decreased from 11 to 8% at year 1 and 6.4% at year 4. Longitudinal analysis showed 53% of patients with DM and elevated IGF-I at baseline achieved IGF-I normalization by year 4, but decrease in IGF-I and glycemic change were not correlated.…”
Section: Pegvisomantmentioning
confidence: 79%
“…Overall, IGF-I control was observed in 71.7% of patients on pegvisomant monotherapy, with tumor growth noted in 7.3% and transaminase elevation in 3.0%. Real-word experiences independent of ACROSTUDY also mirrored these results, despite some country-specific differences in how pegvisomant is used in monotherapy vs combination therapy regimens [78][79][80]°I n 1,762 patients in ACROSTUDY, 29% of whom had DM at baseline (HbA1c ≥ 6.5%, FBG > 200 g/dL, or use of antidiabetic medication) [81], cross-sectional analysis at 4 years of follow-up showed that FBG and HbA1c remained stable in patients without DM, but prevalence of impaired glucose tolerance decreased from 11 to 8% at year 1 and 6.4% at year 4. Longitudinal analysis showed 53% of patients with DM and elevated IGF-I at baseline achieved IGF-I normalization by year 4, but decrease in IGF-I and glycemic change were not correlated.…”
Section: Pegvisomantmentioning
confidence: 79%
“…In the Brazilian study, tumour enlargement was reported in 6.5% of cases (n = 5). In the Argentinian study, 4 of 50 patients (8%) showed an increase in tumour size with pegvisomant ( Table 1) [33]. In the meta-analysis of five studies with pegvisomant in monotherapy, the overall tumour growth rate was 7.2% (4.8-10.7%; 95% CI; I 2 = 0%) [15].…”
Section: Tumour Sizementioning
confidence: 96%
“…In the Brazilian and Argentinian cohort, elevation of liver enzymes was reported in 9% of cases and was responsible for pegvisomant discontinuation in 1 and 5 patients, respectively ( Table 1) [14,33].…”
Section: Hepaticmentioning
confidence: 99%
“…T wo studies published in this present issue of the Archives of Endocrinology and Metabolism, by Natalia Garcia Basavilbaso (1) and coworkers, as well as the one by Cesar Boguszewski and coworkers (2), describe the treatment response in real-life of pegvisomant (PEGV) therapy in acromegaly patients, including aspects of safety and efficacy.…”
mentioning
confidence: 99%
“…Serum IGF-I levels decreased to normal ranges in "only" 63% of patients after a median treatment duration of 27 months, with a daily mean dose of about 12 mg (2). In the Brazilian report, PEGV was used as monotherapy in 11% of the cases, while normal IGF-I levels were obtained in about 75% of patients (1). Why more patients cannot be controlled in the real-life setting of center of excellence?…”
mentioning
confidence: 99%